Respuestas

  • Usuario de Brainly
2013-12-16T19:18:07+01:00
Pares consecutivos: ``x´´ y ``x + 2´´

x² + (x + 2)² = 340
x² + x² + 4x + 4 = 340
2x² + 4x + 4 - 340 = 0
2x² + 4x - 336 = 0  ⇒ x² + 2x - 168 = 0

 x = \frac{-2 \frac{+}{} \sqrt{2^2-4*1*(-168)} }{2}

 x = \frac{-2 \frac{+}{} \sqrt{4+672} }{2}

 x = \frac{-2 \frac{+}{} \sqrt{676} }{2}

 x = \frac{-2 \frac{+}{} 26 }{2}

x₁ = (-2 + 26)/2 = 12  ;  x + 2 = 14
x₂ = (-2 - 26)/2 = -14  ;  x + 2 = -12

Tiene dos soluciones, es decir, dos pares de números que cumplen lo que pides:
Soluciones:
Nº 12 y 14
Nº -14 y -12